Natural selection on a carbon cycling trait drives ecosystem engineering by Sphagnum (peat moss). Issue 1957 (25th August 2021) - Piatkowski, Bryan T.; Yavitt, Joseph B.; Turetsky, Merritt R.; Shaw, A. Jonathan
Abstract : Sphagnum peat mosses have an extraordinary impact on the global carbon cycle as they control long-term carbon sequestration in boreal peatland ecosystems. Sphagnum species engineer peatlands, which harbour roughly a quarter of all terrestrial carbon, through peat accumulation by constructing their own niche that allows them to outcompete other plants. Interspecific variation in peat production, largely resulting from differences in tissue decomposability, is hypothesized to drive niche differentiation along microhabitat gradients thereby alleviating competitive pressure. However, little empirical evidence exists for the role of selection in the creation and maintenance of such gradients. In order to document how niche construction and differentiation evolved in Sphagnum, we quantified decomposability for 54 species under natural conditions and used phylogenetic comparative methods to model the evolution of this carbon cycling trait. We show that decomposability tracks the phylogenetic diversification of peat mosses, that natural selection favours different levels of decomposability corresponding to optimum niche and that divergence in this trait occurred early in the evolution of the genus prior to the divergence of most extant species. Our results demonstrate the evolution of ecosystem engineering via natural selection on an extended phenotype, of a fundamental ecosystem process, and one of the Earth's largest soil carbon pools.